2014
DOI: 10.1007/s00134-014-3382-9
|View full text |Cite
|
Sign up to set email alerts
|

Early lung ultrasonography predicts the occurrence of acute respiratory distress syndrome in blunt trauma patients

Abstract: LUS on admission identifies patients at risk of developing ARDS after blunt trauma. In addition, LUS allows rapid and accurate diagnosis of common traumatic thoracic injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 25 publications
(63 reference statements)
0
27
0
Order By: Relevance
“…LU also outperformed CR for the diagnosis of pleural effusion, as previously suggested in other settings. 12,25,26 Radiological imaging has progressed toward an all-digital future, improving image presentation of bedside CR, but without major reduction in the radiation dose, as compared with screen film. 27 The particularly poor sensitivity of CR for the detection of condensations (which were mostly basal) and pleural effusion probably highlights limitations of the silhouette sign.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LU also outperformed CR for the diagnosis of pleural effusion, as previously suggested in other settings. 12,25,26 Radiological imaging has progressed toward an all-digital future, improving image presentation of bedside CR, but without major reduction in the radiation dose, as compared with screen film. 27 The particularly poor sensitivity of CR for the detection of condensations (which were mostly basal) and pleural effusion probably highlights limitations of the silhouette sign.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported a similar advantage of LU over CR in patients with pneumonia, 2931 respiratory distress requiring mechanical ventilation, 32 and those with the acute respiratory distress syndrome. 25,33 The routine use of bedside LU in place of CR may allow reducing radiation exposure in sickle cell disease patients during their lifespan (inasmuch as ACS is typically a relapsing disease), while optimizing lung imaging capabilities. In centers implementing point-of-care ultrasonography, this technique may allow a rapid, readily available, and accurate tool for the follow-up of patients with ACS, as suggested for critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Promising diagnostic advances have been recently proposed, using ultrasound to rule out a cardiogenic source of lung edema and to predict ARDS in blunt trauma patients (29)(30)(31), and using low-dose chest CT to monitor and redirect the treatment strategy of the ventilator setting (32,33). Along with measurements of SpO 2 /FiO 2 by pulseoximetry, in lack of PaO 2 /FiO 2 measurements (34), lung ultrasound (35) can be extremely appealing in settings with limited ICU resources, as lately proposed by the Kigali modification of the Berlin definition (36).…”
Section: History Of Ards: the Long Path To Define A Syndrome-new Acqumentioning
confidence: 99%
“…Particularly in asymptomatic pediatric patients, routine use of CT scans is not recommended for unknown causes of blunt trauma injury [20]. Chest sonography, another option for detecting and estimating the volume of retained hemothorax, can provide rapid and accurate diagnosis of traumatic thoracic injuries, such as lung contusions and pleural collections [21,22]. However, similar to a chest radiograph, ultrasonography is ineffective for diagnosing mediastinal hematoma, which can be easily detected by a CT scan [23].…”
Section: Diagnosis Of Retained Hemothoraxmentioning
confidence: 99%